Effects of formative tests and communicative grammar instruction on EFL students oral response ability - Hadeli, Hadeli; Kustati, Martin; Zulfikar, Teuku; Azmi, Hidayat Al; Arumugam, Nalini (Universitas Syiah Kuala, 2023)
This study investigates the effect of formative exams and communicative grammar teaching strategies on the students oral response-ability. This research had a 2x2 factorial experimental design where 80 third-year university students were assigned using multistage cluster probability random sampling. The data were analyzed using a two-way covariance analysis (ANCOVA) to test the research hypotheses. The study outcomes demonstrated that students taught with constructive formative tests had higher achievement than those receiving the selective formative examination. The result indicated that deductive learning with concept maps was more effective in improving students ability of communicative competence compared to inductive learning. Additionally, this study found that students taught with deductive grammar instructional strategy accompanied by English concept maps demonstrated higher achievement in communicative competence than those taught with inductive grammar instructional strategy in the group of students treated with the selective formative test. Deductive learning procedures with concept maps had positive impacts from the inductive strategy to the student capacity to respond orally among students who were given constructive formative examinations. Notably, the effectiveness of various sub-instructional tactics and sub-formative test combinations on students verbal response capacity varied. Thus, English teachers must create formative examinations by considering constructive formative tests. Based on the research findings, recommendations for how teachers can improve students oral-response ability by adopting appropriate assessments using more deductive learning are discussed.